On k-Distance Pell Numbers in 3-Edge-Coloured Graphs - Krzysztof Piejko; Iwona Włoch (Journal of Applied Mathematics)
We define in this paper new distance generalizations of the Pell numbers and the companion Pell numbers. We give a graph interpretation of these numbers with respect to a special 3-edge colouring of the graph.